Spatial variability of water infiltration rate in soil under pasture as a function of cattle trampling intensity - Miguel, Fernanda Ribeiro Marques; Vieira, Sidney Rosa; Grego, Célia Regina (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to evaluate the effect of cattle trampling intensity on the spatial variability of soil-water infiltration rate. The experiment was carried out on an Argissolo Vermelho-Amarelo (Ultisol) under a Urochloa brizantha pasture, divided into six one-hectare plots, each with 50 sampling points in a 10x10 m grid. In each sampling site, the saturated three-dimensional infiltration rate at 0.10 and 0.20-m depths was measured. Measurements were made in the first, eleventh and fifteenthcattle passages on the plots. Data were submitted to geostatistics for the study of the spatial variability of the saturated infiltration rate. The 15 cattle passages on the plots caused a decrease of 73.3% in the soil water infiltration rate, at 0.10-m depth, and 64.4% at 0.20-m depth. The study of spatial variability of soil-water infiltration rate with geostatistics permits the construction of maps for assessing the effects of cattle trampling intensification on soil physical properties. Water infiltration rate in soil has a spatial dependency structure which increases as a function of trampling intensity.